Swot analysis as a facilitator of strategic process management at the port of Vila do Conde - Nunes, Lohanna Monteiro; Carneiro, Igor Bitencourt; Turiel, Lisabelly Cardoso de Farias; Lopes, Harlenn dos Santos; Martins, Harley dos Santos (Brazilian Journal of Production Engineering, 2025)
Ports play a crucial role in the global logistics market and are essential for the international transportation of cargo. Port efficiency is fundamental to national competitiveness, reducing export tariffs and benefiting foreign trade. In Pará, the geography favors cargo handling, and the Port of Vila do Conde, one of the largest in the country, faces challenges such as the lack of adequate reports and KPIs to evaluate its operations and management. This study proposes process mapping to solve standardization problems in the incorporation and invoicing process, using the SWOT matrix and the KANBAN model. The aim is to optimize these processes by standardizing and monitoring activities, increasing efficiency and serving as a benchmark for national ports. The results indicate that the standardization of processes makes it possible to carry out services without losses, reducing costs and improving billing in a more efficient and advantageous way for the company.